Prediction of adverse clinical outcome in patients with acute pulmonary embolism: evaluation of high-sensitivity troponin I and quantitative CT parameters - Apfaltrer, Paul; Walter, Thomas; Grüttner, Joachim; Weilbacher, Frank; Meyer, Mathias; Henzler, Thomas; Neumaier, Michael; Schönberg, Stefan; Fink, Christian (European journal of radiology, 2013)
PURPOSE: To evaluate the accuracy of high-sensitivity-cardiac-troponin-I (hs-cTnI) and quantitative CT-parameters, alone and in combination, for predicting right-ventricular-dysfunction (RVD) and adverse clinical outcome in patients with acute pulmonary embolism (PE). MATERIALS AND METHODS: 65 patients with PE and hs-cTnI measurements within 24 h of CT were retrospectively included. RVD was assessed on CT by calculating right ventricular/left ventricular (RV/LV) diameter ratios on transverse sections (RV/LVtrans), four-chamber-views (RV/LV4ch), and RV/LV volume ratio (RV/LVvol). Pulmonary CTA-obstruction-scores (OS) (Qanadli, Mastora) were calculated. Receiver operator characteristic (ROC) analysis was performed to compare Hs-cTnI, RV/LV ratios, and OS for predicting adverse clinical outcome (i.e. intensive care treatment, death). RESULTS: 12 patients with PE had adverse clinical outcome and showed significantly higher RV/LV ratios and OS compared to those without. ROC analysis revealed a cutoff value of 0.042 ng/mL for hs-cTnI resulting in a sensitivity and specificity of 84% and 92% for predicting adverse clinical outcome, respectively. Elevated hs-cTnI was significantly associated with adverse clinical outcome. In a ROC analysis the AUC for the prediction of adverse clinical outcome of RV/LV4Ch, RV/LVvol, and hs-cTnI were 0.77, 0.76, and 0.71. The combination of hs-cTnI and RV/LV ratios increased the AUC for the prediction of adverse clinical outcome. CONCLUSIONS: Hs-cTnI is associated with adverse clinical outcome in patients with acute PE. A combination of hs-cTnI with quantitative CT-parameters improves the prediction of adverse clinical outcome.
Available online 10 December 2012k
Gesehen am 28.06.2018